2004
DOI: 10.1002/ejoc.200400237
|View full text |Cite
|
Sign up to set email alerts
|

Stereo‐ and Regiocontrol in the Formation of Lactams by Rhodium‐Carbenoid C−H Insertion of α‐Diazoacetamides

Abstract: The dirhodium(II)‐catalysed intramolecular C−H insertion reaction of α‐diazoacetamides is a powerful methodology for the preparation of highly valuable heterocyclic compounds such as lactams. In this Microreview we present lactam formation by intramolecular C−H insertion of α‐diazoacetamides, focusing on the effects that have a profound impact on the reaction pathway. (© Wiley‐VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0
3

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(46 citation statements)
references
References 99 publications
1
42
0
3
Order By: Relevance
“…[28] The appearance of b-lactams in cyclizations of diazoacetamides is caused by the activation of a C À H bond adjacent to the nitrogen atom. [20,29] In addition, the nature of the catalyst can influence the regioselectivity and chemoselectivity of the carbenoid reaction; [1,8,30] e.g., in carbenoid cyclizations of diazoacetamides, the transition from Rh 2 (acetamide) 4 to Rh 2 A C H T U N G T R E N N U N G (acetate) 4 and Rh 2 (perfluorobutyrate) 4 as catalyst, corresponding to a change towards a more electro- Table 3. Catalytic decomposition of N,N-dibutyldiazoacetamide (3b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] The appearance of b-lactams in cyclizations of diazoacetamides is caused by the activation of a C À H bond adjacent to the nitrogen atom. [20,29] In addition, the nature of the catalyst can influence the regioselectivity and chemoselectivity of the carbenoid reaction; [1,8,30] e.g., in carbenoid cyclizations of diazoacetamides, the transition from Rh 2 (acetamide) 4 to Rh 2 A C H T U N G T R E N N U N G (acetate) 4 and Rh 2 (perfluorobutyrate) 4 as catalyst, corresponding to a change towards a more electro- Table 3. Catalytic decomposition of N,N-dibutyldiazoacetamide (3b).…”
Section: Resultsmentioning
confidence: 99%
“…Rhodium-catalyzed transformations of a-diazoacetamides into lactams via C À H insertion are popular as well and have been reviewed recently. [8,9] Currently ruthenium complexes are receiving growing attention as catalysts for carbenoid transformations. [10][11][12][13] Che and co-workers have shown that ruthenium porphyrins are effective catalysts for cyclization of tosylhydrazones via intramolecular carbenoid C À H insertion; [14,15] inter alia, b-lactams were obtained in high yields and with excellent stereoselectivity from N-alkyl-N-tert-butyl 3-(tosylhydrazono)acetoacetamides.…”
Section: Introductionmentioning
confidence: 99%
“…Previamente à realização deste trabalho, os alunos foram aconselhados a consultar a literatura mais recente e relevante acerca das reacções de inserção C-H de compostos diazo catalisadas por complexos de ródio (II) 22,24,25 e em particular à aplicação desta metodologia em água 43,44 . Para executar o passo de formação da α-diazo acetamida, foi necessário preparar a p-toluenossulfonil azida (2), tendo esta sido obtida em 80% de rendimento (Esquema 1), e que no segundo passo da síntese seria utilizada como agente de introdução da unidade diazo.…”
Section: Resultsunclassified
“…Para contornar este problema, actualmente utilizam-se metais que reagem como electrófilos com o composto diazo dando origem a um metalocarbeno menos reactivo e consequentemente mais selectivo 21 . Apesar de vários metais possuírem a capacidade de se coordenar com carbenos, os catalisadores binucleares de ródio com ligandos carboxilato têm-se evidenciado pela elevada eficiência e selectividade, demonstrada nas reacções de inserção C-H de compostos α-diazo carbonílicos, em particular quando aplicados na sín-tese de compostos quirais [22][23][24][25] . Apesar da grande utilidade destas reacções, estas são frequentemente executadas em solventes orgânicos de forma a manter a mistura reaccional em condições homogéneas.…”
Section: Introductionunclassified
See 1 more Smart Citation